Lithium ion supercapacitor and preparation method thereof

By making micropores on the surface of the positive and negative electrode foil of the lithium-ion capacitor, and optimizing the distribution of slurry and electrolyte, the problems of low pre-embedding of lithium-ion capacitors and instability of materials are solved, and higher energy density and Cycling life reduces manufacturing costs.

CN119208026APending Publication Date: 2024-12-27JIANGXI ZHANXIAO NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411239646.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Lithium ion capacitors have problems such as unevenness, unstable material structure and high manufacturing costs in pre-embedded lithium technology, resulting in low energy density and reduced cycle life.

Method used

By creating micropores on the surface of positive and negative electrode foils, the slurry coating volume and electrolyte permeability efficiency are improved, and the porous structure and specific material ratio are used to optimize the construction of electrode layers and the selection of electrolytes to achieve rapid lithium ions. Transmission and uniform lithium embedding.

Benefits of technology

It improves the energy density and cycle life of lithium-ion supercapacitors, shortens the pre-embedded lithium time, reduces manufacturing costs, and improves the energy efficiency and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208026A_ABST
    Figure CN119208026A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion supercapacitor and a preparation method thereof, and belongs to the technical field of capacitors. The method comprises the following steps: respectively manufacturing micropores in the surfaces of a positive electrode foil and a negative electrode foil to obtain a porous positive electrode foil and a porous negative electrode foil; coating the surface, with the micropores, of the porous positive electrode foil with positive electrode slurry to obtain a positive plate, and coating the surface, with the micropores, of the porous negative electrode foil with negative electrode slurry to obtain a negative plate; a lithium supplementing piece, the negative plate, a diaphragm and the positive plate are sequentially stacked and packaged in a shell, and the lithium ion supercapacitor is obtained through electrolyte injection, lithium pre-embedding, formation and capacity grading. The capacitor prepared by the method has relatively high energy density, the lithium pre-embedding time can be shortened, and a relatively uniform lithium embedding interface can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery containers, and in particular to a lithium ion supercapacitor and a preparation method thereof. Background Art

[0002] Lithium-ion capacitors are energy storage devices that combine the high energy density of lithium-ion batteries with the high power density of supercapacitors. However, there are some inefficiencies in pre-lithium technology. Pre-lithium technology refers to the pre-embedding of lithium ions during the manufacturing process of the capacitor to increase its energy density. However, this technology has encountered some challenges in practical applications. First, the inhomogeneity in the pre-lithium process can lead to uneven distribution of lithium ions inside the capacitor, which in turn affects its charge and discharge efficiency. Second, lithium ions may cause instability in the material structure during the embedding and de-embedding process, resulting in a reduced cycle life of the capacitor. In addition, pre-lithium embedding may also increase manufacturing costs and complexity. To address these issues, researchers are exploring new materials and manufacturing processes to improve the performance and reliability of lithium-ion capacitors. Summary of the invention

[0003] The main purpose of the present invention is to provide a lithium ion supercapacitor and a preparation method thereof, so as to solve the technical problems of long lithium pre-embedding time and low energy density of lithium ion battery containers.

[0004] To achieve the above object, the present invention provides a method for preparing a lithium ion supercapacitor, comprising the following steps:

[0005] S10, making micropores on the surface of the positive electrode foil and the negative electrode foil respectively to obtain a porous positive electrode foil and a porous negative electrode foil;

[0006] S20, applying positive electrode slurry to the surface of the porous positive electrode foil with the micropores to obtain a positive electrode sheet, and applying negative electrode slurry to the surface of the porous negative electrode foil with the micropores to obtain a negative electrode sheet;

[0007] S30, stacking the lithium supplement sheet, the negative electrode sheet, the separator, and the positive electrode sheet in order and encapsulating them inside the shell, injecting electrolyte, pre-embedding lithium, forming, and dividing the capacity to obtain the lithium ion supercapacitor.

[0008] In some embodiments of the present invention, the pore size of the micropores in the porous positive electrode foil is 50 μm to 80 μm; and / or the pore size of the micropores in the porous negative electrode foil is 50 μm to 80 μm.

[0009] In some embodiments of the present invention, the pore spacing of micropores in the porous positive electrode foil is 100 μm to 150 μm; and / or the pore spacing of micropores in the porous negative electrode foil is 100 μm to 150 μm.

[0010] In some embodiments of the present invention, the material of the positive electrode includes carbon-coated aluminum; and / or the material of the negative electrode includes copper foil.

[0011] In some embodiments of the present invention, the positive electrode slurry includes a positive electrode active material, a conductive agent and a binder.

[0012] In some embodiments of the present invention, the positive electrode active material includes lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium sulfur silicate;

[0013] And / or, the conductive agent includes at least one of carbon black, conductive graphite, carbon nanotubes, and graphene;

[0014] And / or, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber;

[0015] And / or, the mass ratio of the positive electrode active material, the conductive agent, and the binder is (50-90): (3-10): (3-20).

[0016] In some embodiments of the present invention, the negative electrode active material includes at least one of graphite, silicon material, and hard carbon;

[0017] And / or, the conductive agent includes at least one of acetylene black, carbon black, carbon nanotubes, and graphene;

[0018] And / or, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber;

[0019] And / or, the mass ratio of the negative electrode active material, the conductive agent, and the binder is (50-90):(3-30):(3-20).

[0020] In some embodiments of the present invention, the electrolyte includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium perchlorate (LiClO4).

[0021] The present invention also provides a lithium ion supercapacitor prepared according to the preparation method as described above. The beneficial effects that can be achieved by the present invention are:

[0022] The present invention increases the coating amount of positive and negative electrode slurries and improves the energy density of the capacitor by forming holes on the surfaces of the positive and negative electrode foils. The microporous channels formed after the holes are formed can also facilitate the infiltration of the electrolyte into the electrodes and the rapid transmission of lithium ions, thereby improving the pre-lithium embedding efficiency and shortening the pre-lithium embedding time. The electrolyte covers the surface of the negative electrode more evenly, and it is also easy to obtain a relatively uniform lithium embedding interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0024] Figure 1 The present invention is a schematic diagram of the preparation process of a method for preparing a lithium ion supercapacitor.

[0025] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0026] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0029] The present invention provides a method for preparing a lithium ion supercapacitor, referring to Figure 1 , including the following steps:

[0030] S10, making micropores on the surface of the positive electrode foil and the negative electrode foil respectively to obtain a porous positive electrode foil and a porous negative electrode foil;

[0031] S20, applying positive electrode slurry to the surface of the porous positive electrode foil with the micropores to obtain a positive electrode sheet, and applying negative electrode slurry to the surface of the porous negative electrode foil with the micropores to obtain a negative electrode sheet;

[0032] S30, stacking the lithium supplement sheet, the negative electrode sheet, the separator, and the positive electrode sheet in sequence and encapsulating them inside the shell, injecting electrolyte, pre-embedding lithium, forming, and dividing the capacity to obtain the lithium ion supercapacitor. The present invention forms holes in the positive electrode foil to obtain a porous positive electrode foil, and coats the positive electrode slurry on the surface of the porous positive electrode foil with micropores to obtain a positive electrode sheet containing a positive electrode active layer, which can increase the coating amount of the positive electrode slurry, which is beneficial to improving the energy density of the capacitor, and forms holes in the negative electrode foil to obtain a porous negative electrode foil, and coats the negative electrode slurry on the surface of the porous negative electrode foil with micropores to obtain a negative electrode sheet containing a negative electrode active layer, which can increase the coating amount of the negative electrode slurry, and in the same battery volume, more active substances can be accommodated, the energy density of the battery is improved, and the capacitor of the same volume can store more electrical energy, providing higher energy efficiency for applications such as electric vehicles and energy storage devices. In addition, the surface of the positive and negative electrode foils has a higher specific surface area after pores are formed, which can provide more anchor points for the attachment of positive and negative electrode slurries. The positive and negative electrode slurries can better penetrate into the micropores of the foils to form a strong bond, thereby strengthening the bonding force between the positive and negative electrode slurries and the foils, effectively reducing the shedding of active substances, and improving the cycle life and safety of the battery. The microporous structure can also promote the penetration of the electrolyte and provide a fast transmission channel for the transmission of lithium ions, thereby achieving the effect of accelerating the efficiency of pre-embedded lithium.

[0033] In some embodiments, the pore size of the micropores in the porous positive electrode foil is 50μm to 80μm, and can be 50μm, 60μm, 70μm, 80μm, etc., in the range of 50μm to 80μm. There will be no material falling due to the excessively large pore size, nor will the coating amount of the slurry be reduced due to the excessively small pore size. In addition, the mechanical strength of the foil can be ensured, making the foil less likely to deform and rupture.

[0034] In some embodiments, the pore size of the micropores in the porous negative electrode foil is 50μm to 80μm, and can be 50μm, 60μm, 70μm, 80μm, etc., in the range of 50μm to 80μm. There will be no material falling due to the excessively large pore size, nor will the coating amount of the slurry be reduced due to the excessively small pore size. In addition, the mechanical strength of the foil can be ensured, making the foil less likely to deform and rupture.

[0035] In the present invention, the micropores in the positive electrode foil and the negative electrode foil are arranged equidistantly, which can optimize the flow path of the electrolyte, increase the contact area between the electrolyte and the active material in the electrode sheet, and promote the uniform distribution of the active material in the active layer, reduce the local overheating caused by excessive local active material, and reduce the risk of thermal runaway of the capacitor.

[0036] In some embodiments, the pore spacing of the micropores in the porous positive electrode foil is 100 μm to 150 μm, for example, it can be any value in the range of 100 μm to 150 μm, such as 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, etc. Under the above pore spacing range conditions, it is conducive to uniform slurry coating and formation of a uniform active layer, and the micropores are more evenly distributed, which is conducive to the formation of a uniform lithium insertion interface.

[0037] In some embodiments, the pore spacing of the micropores in the porous negative electrode foil is 100 μm to 150 μm, for example, it can be any value in the range of 100 μm to 150 μm, such as 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, etc. Under the above pore spacing range conditions, it is conducive to uniform slurry coating and forming a uniform active layer.

[0038] In some embodiments, the depth of the micropores in the positive electrode foil is 50% to 80% of the thickness of the foil, and can be any value within the range of 50% to 80%, such as 50%, 60%, 70%, or 80%.

[0039] In some embodiments, the foil may be pore-formed by a laser device, thereby producing micropores with uniform distribution and small pore size, which are not likely to damage the structure of the foil itself.

[0040] In some embodiments, after the positive electrode slurry or the negative electrode slurry is coated on the surface of the foil to form the positive electrode active layer and the negative electrode active layer respectively, a PET film is laid on the surface of the positive electrode active layer and the negative electrode active layer, and then rolled. This can avoid leakage and enhance the filling of micropores in the foil.

[0041] In some embodiments, the material of the positive electrode includes carbon-coated aluminum foil, holes are made on the surface of the carbon-coated aluminum foil, and then the positive electrode slurry is coated on the surface with micropores to obtain a positive electrode sheet. In this embodiment, micropores are made on the surface of the carbon-coated aluminum foil provided with a carbon layer. In this embodiment, the carbon-coated aluminum foil is used as the current collector of the positive electrode, and the carbon layer covering its surface can effectively improve the conductivity of the positive electrode sheet, improve the electron transmission efficiency, and reduce the internal resistance of the battery. In addition, the carbon-coated aluminum foil has good mechanical strength, which can overcome the damage to the foil itself during the hole-making process.

[0042] In some embodiments, the positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium sulfur silicate.

[0043] In some embodiments, the positive electrode active material is lithium sulfur silicate, which can achieve rapid replenishment of active lithium without sacrificing the energy density of the battery cell, and improve ionic conductivity and pre-lithium embedding rate.

[0044] In some embodiments, the conductive agent includes at least one of carbon black, conductive graphite, carbon nanotubes, and graphene.

[0045] In some embodiments, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber. The above binders can strengthen the bonding force between the positive electrode slurry and the foil, reduce the falling of the positive electrode slurry, and help maintain the excellent energy density of the capacitor.

[0046] In some embodiments, the mass ratio of the positive electrode active material, the conductive agent, and the binder is (50-90): (3-10): (3-20).

[0047] In some embodiments, the negative electrode foil includes copper foil. Pores are formed on the surface of the copper foil, and then the negative electrode slurry is coated on the surface with micropores to obtain a negative electrode sheet containing a negative electrode active layer. The present invention designs the positive and negative electrode sheets, which can not only increase the coating amount of the slurry and improve the energy density of the capacitor, but also the formed microporous structure can enhance the infiltration of the electrolyte, improve the pre-lithium insertion efficiency, and reduce the pre-lithium insertion time.

[0048] In some embodiments, the negative electrode slurry includes a negative electrode active material, a conductive agent, and a binder.

[0049] In some embodiments, the negative electrode active material includes at least one of graphite, silicon material, and hard carbon.

[0050] In some embodiments, the conductive agent includes at least one of acetylene black, carbon black, carbon nanotubes, and graphene.

[0051] In some embodiments, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber. With the help of the above binders, it is beneficial to strengthen the bonding force between the negative electrode slurry and the foil, reduce the falling of the slurry, and facilitate the introduction of the electrolyte, enhance the infiltration of the electrolyte, and improve the pre-lithium embedding efficiency.

[0052] In some embodiments, the mass ratio of the negative electrode active material, the conductive agent, and the binder is (50-90):(3-30):(3-20).

[0053] In some embodiments, the negative electrode slurry further includes titanate (Li4Ti5O 12 ), adding porous titanate to the negative electrode slurry has high stability and rapid lithium ion diffusion ability, improves the pre-lithium embedding efficiency and shortens the pre-lithium embedding time.

[0054] In some embodiments, the titanate includes porous titanate. The porous titanate has abundant pores and can form microporous channels in the negative electrode active layer, so that the microporous channels and the micropores of the negative electrode foil are connected to form a network-like microporous structure, thereby enhancing the infiltration of the electrolyte into the negative electrode sheet. In the pre-lithium insertion process, lithium ions are rapidly transmitted with the help of the network-like microporous structure, which shortens the lithium insertion time and forms a uniform lithium insertion interface.

[0055] In some embodiments, the porosity of the porous titanate is 50% to 70%, which can be any value in the range of 50%, 60%, 70%, etc. Under the above porosity conditions, it is beneficial to form abundant microporous channels in the negative electrode active layer, so that the microporous channels and the micropores of the negative electrode foil are connected, thereby enhancing the infiltration of the electrolyte into the negative electrode sheet, accelerating the transmission of lithium ions, and increasing the speed of pre-lithium embedding.

[0056] In some embodiments, the mass ratio of the negative electrode active material, the conductive agent, the binder and the titanate is (50-90): (3-30): (3-20): (10-20). Under the above ratio conditions, it is beneficial to provide rapid lithium ion diffusion capacity, improve pre-lithium insertion efficiency, and shorten the pre-lithium insertion time. In this embodiment, when the titanate is a porous titanate, it is beneficial to form abundant microporous channels on the surface of the negative electrode active layer, so that the microporous channels and the micropores of the negative electrode foil are connected, the electrolyte infiltration into the negative electrode sheet is enhanced, the transmission of lithium ions is accelerated, and the pre-lithium insertion speed is increased.

[0057] In some embodiments, the negative electrode active layer on the negative electrode sheet includes a first negative electrode active layer and a second negative electrode active layer, the porosity of the first negative electrode active layer is less than the porosity of the second negative electrode active layer, the first negative electrode active layer is disposed on the surface of the negative electrode sheet current collector, and the second negative electrode active layer is disposed on the surface of the first negative electrode active layer away from the current collector. The first negative electrode active layer has a smaller porosity, which can improve the filling effect of the micropores on the surface of the negative electrode foil and reduce the drop of the slurry, while the second negative electrode active layer has a larger porosity, can form microchannels, and is connected to the micropores of the negative electrode foil, thereby enhancing the infiltration of the electrolyte, guiding the rapid transmission of lithium ions, and improving the efficiency of pre-embedded lithium. In this embodiment, the porosity of the first negative electrode active layer can be controlled to be less than the porosity of the second negative electrode active layer by controlling the content of porous titanate in the first negative electrode slurry and the second negative electrode slurry. Illustratively, the mass ratio of the negative electrode active material, the conductive agent, the binder and the porous titanate in the first negative electrode slurry is (50-90):(3-30):(3-20):(0-10), and the mass ratio of the negative electrode active material, the conductive agent, the binder and the porous titanate in the second negative electrode slurry is (50-90):(3-30):(3-20):(15-20).

[0058] In some embodiments, the electrolyte includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium perchlorate (LiClO4).

[0059] In some embodiments, the electrolyte contains additives, and the additives include at least one of polypyrrole, polyaniline, polydioxythiophene, polyethylene oxide, polyvinyl alcohol, and polyacrylic acid. The above types of additives have good electrochemical redox reversibility and affinity, can form efficient ion transmission channels in the electrolyte, can improve the transmission rate of lithium ions, and can promote the rapid migration of lithium ions at the interface between the electrode and the electrolyte, thereby accelerating the pre-lithium insertion process, shortening the pre-lithium insertion time, and optimizing the overall performance of the capacitor.

[0060] In some embodiments, the additive is added in an amount of 1% to 2% of the electrolyte.

[0061] In some embodiments, the pre-lithium insertion time after the capacitor is injected with liquid is 10 to 15 days, which can be 10 days, 11 days, 12 days, 13 days, 14 days, 15 days, etc. Under the condition of short-time pre-lithium insertion, a uniform lithium insertion interface can be obtained, and a better lithium insertion effect can be achieved.

[0062] In some embodiments, the negative electrode sheet of the capacitor is electrically connected to the lithium supplement sheet, and discharged at -30°C to 60°C for 10 to 15 days to complete the pre-lithium insertion of the negative electrode.

[0063] In the present invention, after the pre-lithium insertion is completed, the formation and capacity division can be performed by referring to the conventional technical means in the art.

[0064] In some embodiments, the lithium supplement sheet includes a separator, a copper foil, a lithium sheet, and a cellulose film.

[0065] In some embodiments, a separator, a copper foil, a lithium sheet and a cellulose film are stacked in sequence to obtain a lithium supplement sheet.

[0066] In some embodiments, the cellulose film in the lithium supplement sheet obtained by sequentially stacking the separator, the copper foil, the lithium sheet and the cellulose film faces the negative electrode sheet.

[0067] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0068] Example 1

[0069] Preparation of positive electrode

[0070] Cut the carbon-coated aluminum foil to a suitable size, use laser equipment to prepare micropores with a pore depth of 50%, a pore diameter of 50 μm, and a pore spacing of 100 μm on one side of the carbon-coated aluminum foil. Add the positive electrode active material lithium iron phosphate, the conductive agent conductive graphite and the binder polyvinylidene fluoride into water in a mass ratio of 90:10:20 and disperse them evenly to prepare a positive electrode slurry. Apply the positive electrode slurry to the surface of the carbon-coated aluminum foil with micropores, and then cover it with a PET film. After rolling, a positive electrode sheet with a positive electrode active layer is obtained.

[0071] Preparation of negative electrode

[0072] Cut a copper foil of appropriate size, use a laser device to prepare micropores with a pore depth of 50%, a pore diameter of 50 μm, and a pore spacing of 100 μm on one surface of the copper foil, add negative electrode active material graphite, conductive agent acetylene black, and binder polytetrafluoroethylene into water in a mass ratio of 90:10:20 and disperse them evenly to prepare negative electrode slurry, apply the negative electrode slurry to the surface of the carbon-coated aluminum foil with micropores, and then cover it with a PET film, and roll it to obtain a positive electrode sheet with a positive electrode active layer.

[0073] Assembling capacitors

[0074] The separator, copper foil, lithium sheet and cellulose membrane are stacked in sequence to obtain a lithium supplement sheet.

[0075] The lithium supplement sheet, negative electrode sheet, separator and positive electrode sheet are stacked in sequence and packaged inside the shell, wherein the cellulose film in the lithium supplement sheet faces the negative electrode sheet, and then the electrolyte lithium hexafluorophosphate is injected, the negative electrode sheet and the lithium supplement sheet of the capacitor are electrically connected, and discharged at -30℃ to 60℃ for 15 days to complete the pre-lithium embedding of the negative electrode, and then the lithium ion supercapacitor is obtained through formation and capacity division.

[0076] Example 2

[0077] Example 2 A lithium-ion supercapacitor is prepared by referring to the preparation method of Example 1, but the difference is that the formula of the negative electrode slurry in Example 2 is as follows: the negative electrode active material graphite, the conductive agent acetylene black, the binder polytetrafluoroethylene and the porous titanate with a porosity of 50% to 70% are added to water in a mass ratio of 90:10:20:20 and dispersed evenly to prepare the negative electrode slurry.

[0078] Example 3

[0079] Example 3 A lithium-ion supercapacitor is prepared by referring to the preparation method of Example 1, but the difference is that in the step of preparing the negative electrode sheet, a first negative electrode slurry and a second negative electrode slurry are prepared, the first negative electrode slurry is coated on the surface of the copper foil having micropores and rolled to form a first negative electrode active layer, and then the second negative electrode slurry is coated on the surface of the first negative electrode active layer, and the second negative electrode active layer is obtained by rolling with the same rolling parameters.

[0080] Among them, the first negative electrode slurry contains negative electrode active material graphite, conductive agent acetylene black, binder polytetrafluoroethylene and porous titanate with a porosity of 50% to 70% in a mass ratio of 90:10:20:3, and the second negative electrode slurry contains negative electrode active material graphite, conductive agent acetylene black, binder polytetrafluoroethylene and porous titanate with a porosity of 50% to 70% in a mass ratio of 90:10:20:20. The negative electrode sheet prepared in this way contains a first negative electrode active layer and a second negative electrode active layer, and the second negative electrode active layer has a richer microporous structure.

[0081] Example 4

[0082] Example 4 A lithium ion supercapacitor was prepared by referring to the preparation method of Example 1, except that the electrolyte composition of Example 3 was lithium hexafluorophosphate and polypyrrole, and the mass ratio of lithium phosphate to polypyrrole was 99:1.

[0083] Comparative Example 1

[0084] Comparative Example 1 A lithium-ion supercapacitor was prepared by referring to the preparation method of Example 1, except that in Comparative Example 1, carbon-coated aluminum foil for the positive electrode foil and pores were not formed on copper foil for the negative electrode foil.

[0085] Performance Testing

[0086] The energy density of the capacitors prepared in Examples 1 to 4 and Comparative Example 1 and the capacity retention rate after 5000 cycles of cycle testing at a current density of 1 A / g were tested. The test results are shown in Table 1.

[0087] Table 1

[0088] Experimental Group Energy density (Wh / kg) Capacity retention rate after 5000 cycles (%) Example 1 87 92 Example 2 90 93 Example 3 95 96 Example 4 89 94 Comparative Example 1 81 85

[0089] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a lithium ion supercapacitor, characterized in that: The following steps are involved: S10, making micropores on the surface of the positive electrode foil and the negative electrode foil respectively to obtain a porous positive electrode foil and a porous negative electrode foil; S20, applying positive electrode slurry to the surface of the porous positive electrode foil with the micropores to obtain a positive electrode sheet, and applying negative electrode slurry to the surface of the porous negative electrode foil with the micropores to obtain a negative electrode sheet; S30, stacking the lithium supplement sheet, the negative electrode sheet, the separator, and the positive electrode sheet in order and encapsulating them inside the shell, and obtaining the lithium ion supercapacitor through injecting electrolyte, pre-embedding lithium, forming, and dividing the capacity.

2. The method for preparing a lithium ion supercapacitor according to claim 1, characterized in that: The pore size of the micropores in the porous positive electrode foil is 50 μm to 80 μm; and / or the pore size of the micropores in the porous negative electrode foil is 50 μm to 80 μm.

3. The method for preparing a lithium ion supercapacitor according to claim 1, characterized in that: The inter-pore distance between micropores in the porous positive electrode foil is 100 μm to 150 μm; and / or the inter-pore distance between micropores in the porous negative electrode foil is 100 μm to 150 μm.

4. The method for preparing a lithium ion supercapacitor according to claim 1, characterized in that: The material of the positive electrode includes carbon-coated aluminum; and / or the material of the negative electrode includes copper foil.

5. The method for preparing a lithium ion supercapacitor according to claim 1, characterized in that: The positive electrode slurry includes a positive electrode active material, a conductive agent and a binder.

6. The method for preparing a lithium ion supercapacitor according to claim 5, characterized in that: The positive electrode active material includes lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium sulfur silicate; And / or, the conductive agent includes at least one of carbon black, conductive graphite, carbon nanotubes, and graphene; And / or, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber; And / or, the mass ratio of the positive electrode active material, the conductive agent and the binder is (50-90): (3-10): (3-20).

7. The method for preparing a lithium ion supercapacitor according to claim 1, characterized in that: The negative electrode slurry includes a negative electrode active material, a conductive agent and a binder.

8. The method for preparing a lithium ion supercapacitor according to claim 7, characterized in that: The negative electrode active material includes at least one of graphite, silicon material, and hard carbon; And / or, the conductive agent includes at least one of acetylene black, carbon black, carbon nanotubes, and graphene; And / or, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber; And / or, the mass ratio of the negative electrode active material, the conductive agent and the binder is (50-90):(3-30):(3-20).

9. The method for preparing a lithium ion supercapacitor according to claim 1, characterized in that: The electrolyte includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.

10. A lithium ion supercapacitor prepared according to any one of the preparation methods of claims 1 to 9.